Needs Analysis of Indonesian-Chinese Interpreting Class: A Case Study of X University in Bandung - Limuria, Rika; Sutandi, Septerianie (Language Circle: Journal of Language and Literature, 2022)
The increased collaboration between Indonesia and China in various fields should be supported by sound and effective communication between the two parties. This partnership strongly affects the demand on Indonesian-Chinese translator and/or interpreter. The demand on interpreters are increasing rapidly, ranges from various sectors. However, Chinese language programs available in Indonesia these days are still at the undergraduate levels. Together with the increasing demand on interpreter, various Chinese language study programs are providing translation and/or interpreting courses to equip their students for future job market. As most of the Chinese language students in Indonesia begin to learn Chinese as a foreign language when they are at the university, teaching interpreting at the undergraduate level is certainly challenging compared to teaching interpreting at the postgraduate level. The writers therefore conducts a Needs Analysis on students to find out what are the needs and challenges faced by undergraduate level interpreting trainees, and what kind of curriculum design would suit the undergraduate level interpreting training. This study found that the biggest challenges for the trainees were nervousness during interpreting assignment, difficulty in delivering speech in L2 and L1, and difficulty in understanding L2 input. This study also shows that L2 correlation with trainees’ interpreting performance. The trainees in this study perceive that their foreign language skills affect their performance. Based on the Needs Analysis conducted in this study, the writers also provide suggestions for interpreting course design at the undergraduate level by putting into consideration the number and the linguistic background of students.